Imagining the Great White Mother and the Great King: Aboriginal Tradition and Royal Representation at the “Great Pow-wow” of 1901 - Henry, Wade (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2000)
AbstractThe 1901 Royal Visit to Canada of the Duke and Duchess of Cornwall and York (the future George V and Queen Mary) was marked by a series of ceremonies, not the least of which was the “Great Pow-wow”, staged by more than 2,000 Natives on a wide plateau outside Calgary. More than just an entertaining spectacle, the Great Pow-wow of 1901 was a hegemonic site in which competing representations of Natives, whites, and royalty converged. Officials from the Department of Indian Affairs sought to repress the expression of traditional Aboriginal culture, while other members of the state and a large segment of the press supported the participation of Natives as living examples of the heritage of British justice in Canada. For white Canadians, the pow-wow was an opportunity to define their own identity and imagine their place, and that of Natives, within the nation. At the same time, Natives used the opportunity to resist symbolic control and to ensure their presence and influence within Canada. Like other royal ceremonies, the Great Pow-wow of 1901 served as a contested site in Indian-white relations as both groups structured, manipulated, and imagined representations of themselves, each other, and above all, the monarchy, in order to both maintain and challenge the hegemonic order.